Bone metabolic microarray analysis of ligature‐induced periodontitis in streptozotocin‐induced diabetic mice. (25th April 2016) - Maekawa, S.; Katagiri, S.; Takeuchi, Y.; Komazaki, R.; Ohtsu, A.; Udagawa, S.; Izumi, Y.
Abstract : Background and Objective: Periodontal disease is a chronic infectious disease that results in bone loss. Many epidemiological studies have reported the progression of periodontal tissue destruction in patients with diabetes; however, the associated mechanism remains unclear. In this study, we comprehensively investigated how diabetes affects the periodontal tissue and alveolar bone loss using a ligature‐induced periodontitis model in streptozotocin‐induced diabetic (STZ) mice. Material and Methods: Diabetes was induced by intraperitoneal injection with streptozotocin in 6‐wk‐old C57/BL6J male mice. A silk ligature was tied around the maxillary left second molar in 9‐wk‐old wild‐type (WT) and STZ mice. Bone loss was evaluated at 3 and 7 d after ligation. mRNA expression levels in the gingiva between the two groups were examined by DNA microarray and quantitative polymerase chain reaction at 1, 3 and 7 d post‐ligation. Tartrate‐resistant acid phosphatase and alkaline phosphatase staining of the periodontal tissue was performed for evaluation of osteoclasts and osteoblasts in histological analysis. Results: In the gingiva, hyperglycemia upregulated the osteoprotegerin ( Opg ) mRNA expression and downregulated Osteocalcin mRNA expression. In the ligated gingiva, tumor necrosis factor‐α ( Tnf‐α ) mRNA expression was upregulated at 1 d post‐ligation in STZ mice but not in WT mice. At 3 d post‐ligation, alveolar bone loss was observed in STZ mice, but not in WT mice. Significantly severe alveolar bone loss was observed in STZ mice compared to WT mice at 7 d post‐ligation. Bone metabolic analysis using DNA microarray showed significant downregulation in the mRNA expression of glioma‐associated oncogene homologue 1 ( Gli1 ) and collagen type VI alpha 1 ( Col6a1 ) at the gingiva of the ligated site in STZ mice compared to that in WT mice. Quantitative polymerase chain reaction showed that Gli1 and Col6a1 mRNA expression levels were significantly downregulated in the gingiva of the ligated site in STZ mice compared to WT mice. Histological analysis showed lower alkaline phosphatase activity in STZ mice. In addition, an increased number of tartrate‐resistant acid phosphatase‐positive multinucleated cells were observed at the ligated sites in STZ mice. Conclusions: These results suggest that an imbalance of bone metabolism causes osteoclastosis in insulin‐deficient diabetes, and that alveolar bone loss could occur at an early phase under this condition.